1979
DOI: 10.1085/jgp.73.4.453
|View full text |Cite
|
Sign up to set email alerts
|

The deficit of the isometric tetanic tension redeveloped after a release of frog muscle at a constant velocity.

Abstract: Frog sartorius muscles tetanized isometrically were released at a constant velocity from lengths lL to ls (A/ = l L -ls; ls >/0). The tension P~s redeveloped after the release was lower than the isometric tension Ps at Is, and higher than the isometric tension PL at lL. The tension deficit D is defined as the difference Ps-P*. The timing of the release during the tetanus did not influence D. D/Po was proportional to Al/lo. The proportionality constant k was equal to 1.35 -+ 0.19 (n = 8) when the velocity of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
214
4
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(251 citation statements)
references
References 14 publications
(16 reference statements)
28
214
4
3
Order By: Relevance
“…amount of force obtained in isometric contraction of reference. These speculations are in agreement with the results obtained in some studies (2,6,7,19,32,43).…”
Section: +supporting
confidence: 93%
See 2 more Smart Citations
“…amount of force obtained in isometric contraction of reference. These speculations are in agreement with the results obtained in some studies (2,6,7,19,32,43).…”
Section: +supporting
confidence: 93%
“…This would occur in sites located in two helices of the F-actin chain, which suffer an angular distortion that produce rotation as the muscle is shortened at low speed. Thus, the active site of actin binding is displaced from its original position, preventing the head coupling of heavy mero-myosin or MCP chain (6,7,33,43,44). The proponents of this hypothesis propose that an increase in the rate of cross-bridge uncoupling and an angular distortion, high enough to modify the organization, the structural arrangement and the ideal overlap between the actin-myosin quantity, alter the optimal sarcomere length.…”
Section: Theory Of Stress-induced Inhibition Of Cross Bridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been a continuous search for alternative explanations and several imaginative mechanisms have been proposed (e.g. Maréchal & Plaghki, 1979;Sugi & Tsuchiya, 1988;Granzier & Pollack, 1989;Schachar et al, 2004). The phenomenon of force depression by loaded shortening was revisited by Edman, Caputo & Lou (1993) in frog single muscle fibres using a combination of supplementary techniques to elucidate the possible role of non-uniform sarcomere behaviour.…”
Section: Force Reduction After Loaded Shorteningmentioning
confidence: 99%
“…The fact that shortening has a decremental effect on muscle force during subsequent isometric contractions has been known for decades (Buchtal and Kaiser, 1951;Abbot and Aubert, 1952;Deleze, 1961;Bahler et al, 1968;Joyce and Rack, 1969;Marechal and Plaghki, 1979;van Ingen Schenau et al, 1988) but has found almost no application in muscle and movement modelling. This effect is present regardless of the nature of the shortening phase of the contraction (isokinetic or isotonic contraction).…”
Section: Effects Of Previous Length Changes Of Active Musclementioning
confidence: 99%